Social Capital in Smart Development - Miszczak, Katarzyna (Kapitał społeczny w rozwoju inteligentnym, 2022)
Smart development, primarily based on smart city technologies, also requires the existence of smart communities. Smart communities are influenced by social developments in the community, which are dynamic and determined by individuals’ social levels. Therefore, this study aimed to analyse the use of social capital in building a smart society. The author draws attention to the significance of social capital in terms of social innovations and participation in the sustainable development of the smart city. The article uses the qualitative method analysis i.e. a literature review, and discusses (often critically) the relevance of particular forms, types and functions of social capital to smart development. The author explored how the use of social capital in the community encourages community empowerment and innovative activities and accelerates the development of a smart community. The results confirm that trust, appropriate norms and cooperation among residents affect smart development. Accordingly, social capital is essential in developing smart communities and smart cities. The paper’s original contribution opens the prospects for further research on social capital.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 59-72
Keywords: social capital; social innovations; smart development; smart city; kapitał społeczny; innowacje społeczne; rozwój inteligentny